2016
DOI: 10.4314/ejhs.v26i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Street Foods and Antimicrobial Resistance of Isolates in Hawassa, Ethiopia

Abstract: BACKGROUND: Microbial contamination of ready-to-eat foods and beverages sold by street vendors and hawkers has become an important public health issue. In Ethiopia, health risks related to such kinds of foods are thought to be common. Thus, this study has tried to determine the bacteriological quality of ready-to-eat foods sold on streets. METHODS: A cross-sectional study was conducted on street foods in Hawassa City from May to September 2014. A total of 72 samples from six food items such as local bread ('am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
66
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 14 publications
23
66
14
Order By: Relevance
“…while Study 2 was a broader study which assessed the prevalence of Salmonella, E. coli, and the sanitary quality of RTE foods. The finding of a prevalence of 1.5% S. Enteritidis in study 1 and 1.7% E. coli and 0.0% E. coli O157:H7 and S. Enteritidis in Study 2, is lower than the prevalence rates of Salmonella (2.0-19.7%) and E. coli (6.0-51.5%), reported from Africa (Cardinale et al, 2015;Eromo et al, 2016;Mosupye & von Holy, 1999;Muhammad et al, 2016;Wolde Bereda, Emerie, Reta, & Asfaw, 2016). It is also lower than the prevalence of E. coli (4.1%) and Salmonella (4%) reported from South Korea (Chung, Kim, & Ha, 2010), while comparable with the prevalence data reported for the United States (Levine, Rose, Green, Ransom, & Hill, 2001) and Trinidad and Tobago (Hosein et al, 2008).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…while Study 2 was a broader study which assessed the prevalence of Salmonella, E. coli, and the sanitary quality of RTE foods. The finding of a prevalence of 1.5% S. Enteritidis in study 1 and 1.7% E. coli and 0.0% E. coli O157:H7 and S. Enteritidis in Study 2, is lower than the prevalence rates of Salmonella (2.0-19.7%) and E. coli (6.0-51.5%), reported from Africa (Cardinale et al, 2015;Eromo et al, 2016;Mosupye & von Holy, 1999;Muhammad et al, 2016;Wolde Bereda, Emerie, Reta, & Asfaw, 2016). It is also lower than the prevalence of E. coli (4.1%) and Salmonella (4%) reported from South Korea (Chung, Kim, & Ha, 2010), while comparable with the prevalence data reported for the United States (Levine, Rose, Green, Ransom, & Hill, 2001) and Trinidad and Tobago (Hosein et al, 2008).…”
Section: Discussioncontrasting
confidence: 59%
“…Enteritidis was isolated from fresh salad and starches and not from fish/seafood and meats. Similarly, several authors in Turkey, Ethiopia, and Nigeria have documented the isolation of Salmonella from fresh vegetables and salads with frequencies ranging from 5 to 27% (Agu, Orji, Onuorah, & Anyaegbunam, ; Eromo et al, ; Gurler, Pamuk, Yildirim, & Ertas, ; López‐Campos, Martínez‐Suárez, Aguado‐Urda, & López‐Alonso, ; Wolde, Abate, Sileshi, & Mekonnen, ). In contrast to these findings, a study conducted on RTE foods in Mexico isolated Salmonella most frequently from cooked pork (4.5%) and cooked chicken (3.7%) followed by fresh fruit juices (4%; Zaidi et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(2016) where all isolates were also 100% sensitive to ciprofloxacin. 100% of the isolates were resistant to gentamycin which again contradicts the results of Temesgen et al (2016) which reported 100% of the isolates being susceptible to gentamycin. The fact that bacterial isolates were susceptible to some antibiotics is an indication that the antibiotics remain the drug of choice for the management of most foodborne diseases (Temesgen et al, 2016).…”
Section: Antibiotic Susceptibility Of Bacterial Isolatesmentioning
confidence: 60%
“…In addition, Biswas, Parvez, Shafiquzzaman, Nahar, and Rahman (2010) and Yannick, Rawlings, & Emmanuela (2013) reported the presence of E. coli in RTE meat from Bangladesh (Asia) and Cameroon (Central Africa), respectively, whereas diarrheagenic E. coli strains were recovered from grilled chicken in Burkina Faso (West Africa) (Somda et al, 2018). Similarly, Pseudomonas was detected in street-vended juice in Pakistan, (Batool, Tahir, Rauf, & Kalsoom, 2013), whereas in Bangladesh (Asia) and Ethiopia, Klebsiella was found to contaminate chotpoti and ambasha, respectively (Eromo, Tassew, Daka, & Kibru, 2016;Hassan et al, 2016).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%